Differential microRNA Profile in Operational Tolerance: A Potential Role in Favoring Cell Survival - Cabral, Amanda; da Silva Cândido, Darlan; Monteiro, Sandra Maria; Lemos, Francine; Saitovitch, David; Noronha, Irene L.; Alves, Letícia Ferreira; Geraldo, Murilo Vieira; Kalil, Jorge; Cunha-Neto, Edecio; Pinto Ferreira, Ludmila Rodrigues; Coelho, Verônica (Frontiers in Immunology, 2019)
Background: Operational tolerance (OT) is a state of graft functional stability that occurs after at least 1 year of immunosuppressant withdrawal. MicroRNAs (microRNA) are small non-coding RNAs that downregulate messenger RNA/protein expression of innumerous molecules and are critical for homeostasis. We investigated whether OT in kidney transplantation displays a differential microRNA profile, which would suggest that microRNAs participate in Operational Tolerance mechanisms, and may reveal potential molecular pathways. Methods: We first compared serum microRNA in OT (n = 8) with chronic rejection (CR) (n = 5) and healthy individuals (HI) (n = 5), using a 768-microRNA qPCR-panel. We used the Thermo Fisher Cloud computing platform to compare the levels of microRNAs in the OT group in relation to the other study groups. We performed validation experiments for miR-885-5p, by q-PCR, in a larger number of study subjects (OT = 8, CR = 12, HI = 12), as individual samples. Results: We detected a differential microRNA profile in OT vs. its opposing clinical outcome—CR—suggesting that microRNAs may integrate transplantation tolerance mechanisms. Some miRNAs were detected at higher levels in OT: miR-885-5p, miR-331-3p, miR-27a-5p vs. CR; others, we found at lower levels: miR-1233-3p, miR-572, miR-638, miR-1260a. Considering highly predicted/experimentally demonstrated targets of these miRNAs, bioinformatics analysis revealed that the granzyme B, and death receptor pathways are dominant, suggesting that cell death regulation integrates transplantation tolerance mechanisms. We confirmed higher miR-885-5p levels in OT vs. CR, and vs. HI, in a larger number of subjects. Conclusions: We propose that epigenetics mechanisms involving microRNAs may integrate human transplantation tolerance mechanisms, and regulate key members of the cell death/survival signaling. miR-885-5p could favor cell survival in OT by diminishing the levels of CRADD/RAIDD and CASP3. Nonetheless, given the nature of any complex phenomenon in humans, only cumulative data will help to determine whether this microRNA differential profile may be related to the cause or consequence of operational tolerance.